2020
DOI: 10.3390/atmos11101136
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Microbial Inoculants in a Climate-Changing Agriculture in Eastern Mediterranean Region

Abstract: Climate change has gained importance due to its severe consequences for many aspects of life. Increasing temperature, drought and greenhouse gases affect directly or indirectly the productivity of agricultural and natural ecosystems as well as human health. The nutrient supply capacity of the soil is diminishing, while food requirements for the growing population are increasing. The ongoing application of agrochemicals results in adverse effects on ecosystem functioning and food chain. Now, more than ever, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 167 publications
(181 reference statements)
0
3
0
Order By: Relevance
“…This phenomenon is attributed to the presence of proline in cells, which facilitates chlorophyll synthesis. Low levels of saline-alkali stress promote proline accumulation in cells, thereby stimulating chlorophyll production 19 . www.nature.com/scientificreports/ Furthermore, this study observed a significant increase in the net photosynthetic rate of cotton leaves following inoculation with Funneliformis mosseae and Rhizophagus irregularis.…”
Section: Various Mycorrhizal Fungi Affected Cotton Photosynthesismentioning
confidence: 99%
“…This phenomenon is attributed to the presence of proline in cells, which facilitates chlorophyll synthesis. Low levels of saline-alkali stress promote proline accumulation in cells, thereby stimulating chlorophyll production 19 . www.nature.com/scientificreports/ Furthermore, this study observed a significant increase in the net photosynthetic rate of cotton leaves following inoculation with Funneliformis mosseae and Rhizophagus irregularis.…”
Section: Various Mycorrhizal Fungi Affected Cotton Photosynthesismentioning
confidence: 99%
“…They can sequester greenhouse gases such as carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) from the atmosphere, thus reducing their concentration and mitigating global warming (Kang, 2021). Microorganisms can be harnessed to develop biostimulants and micro/Nano-based formulations that can protect plants against abiotic stresses caused by climate change, such as drought, flooding, and salinity (Athanasia et al, 2020).…”
Section: Climate Change Mitigationmentioning
confidence: 99%
“…The disease can be devastating to susceptible varieties under conducive environmental conditions covering the entire above-ground parts of the plants. The release of ascospores is always associated with high humidity, and therefore, frequent rain is a key factor for the release of ascospores, which are, in fact, the primary inocula (Jones et al, 2014 ; Sawant et al, 2017 ; Kavadia et al, 2020 ). Grapevine diseases can have drastic ill effects not only on the host plants and berries but also on the wine qualities and their sensorial and organoleptic properties (Stummer et al, 2003a , b ; Pinar et al, 2017a , b ), resulting in economic losses for the grape growers and wine producers (van Helden, 2008 ).…”
Section: Introductionmentioning
confidence: 99%